2013
DOI: 10.3390/soc3010080
|View full text |Cite
|
Sign up to set email alerts
|

The Mexican Drug War and the Consequent Population Exodus: Transnational Movement at the U.S.-Mexican Border

Abstract: At the frontline of México’s “war on drugs” is the Mexican-U.S. border city of Cd. Juárez, Chihuahua, which has become internationally known as the “murder capital of the world.” In Juárez, which neighbors El Paso, Texas, United States, estimates of the murders in Juárez are as high as 7,643 between 2006 and 2011, leaving approximately 10,000 orphans. Juárez has also experienced an exodus of approximately 124,000 people seeking safety, some migrating to the Mexican interior and others to the U.S., particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…How gender inequalities played out for families that fled the city due to the violence is an open question that could be investigated in future studies. Interviews with Juárez refugees who now live in El Paso revealed that they face the stress of leaving relatives behind (who do not have crossing visas) and discrimination (Morales et al 2013), but the gendered dimensions of these challenges have yet to be explored.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…How gender inequalities played out for families that fled the city due to the violence is an open question that could be investigated in future studies. Interviews with Juárez refugees who now live in El Paso revealed that they face the stress of leaving relatives behind (who do not have crossing visas) and discrimination (Morales et al 2013), but the gendered dimensions of these challenges have yet to be explored.…”
Section: Resultsmentioning
confidence: 99%
“…Between 2007-2009, Juarez lost 230,000 residents, with 54% of them moving to the US (55,775 residents moved just across the border to El Paso, Texas) and the rest returning to their state of origin (which for the majority of residents is Durango, Coahuila, or Veracruz) (Velázquez Vargas 2012). Those who fled to the US were primarily upper- and middle-class residents (Morales et al 2013). Many residents that remained in the city wished to leave: 42% of residents over 18 surveyed in 2009 were potential migrants, meaning that they desired to migrate to avoid becoming victims of crime, and of this pool, 62% were women who felt vulnerable to crime (Velázquez Vargas 2012).…”
Section: A Methodological Approach To Intersectional Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For Juarez we chose a slow demographic growth scenario given the current context of violence [Morales et al, 2013] (projected average annual growth rates of 1.60% from 2006 to 2012 and 1.06% from 2015 to 2030).…”
Section: Juarezmentioning
confidence: 99%
“…As such, it satisfies the yearning to visit Mexico for nostalgia as discussed earlier. Also, since the outbreak of the cartel wars in Mexico, going to Ciudad Juárez has become more dangerous, deterring many from visiting (Campbell, 2009;Morales, Morales, Menchaca, & Sebastian, 2013).…”
Section: mentioning
confidence: 99%